Sustainability evaluation based on the emergy ecological footprint method: A case study of Qingdao, China, from 2004 to 2014. (February 2018) - Peng, Wenjun; Wang, Xiaoming; Li, Xiaokang; He, Chenchen
Abstract: Urban sustainable development is important for addressing the urgent pressure of ecological transformation in China. This study used an improved emergy ecological footprint method and four indexes to evaluate the sustainability of the complex eco-economic system in Qingdao from 2004 to 2014 by determining the area's emergy carrying capacity and emergy ecological footprint. The results show that Qingdao's per-capita emergy carrying capacity decreased from 12.4305 hm 2 /cap in 2004–11.3295 hm 2 /cap in 2014, with a decrease rate of 0.840%. In contrast, the emergy ecological footprint per capita increased rapidly from 3.0609 hm 2 /cap in 2004–25.4010 hm 2 /cap in 2014, with an increase rate of 21.212%. Thus, the ecological overload increased over time. Qingdao experienced an expanding emergy ecological deficit beginning in 2009. Furthermore, the four sustainability evaluation indexes together indicate that Qingdao was drifting away from sustainability. Moreover, relevant socioeconomic factors were investigated using Pearson correlation analysis, and the results indicate that the largest correlation coefficient exists between the ratio of the output value of tertiary industry to gross regional domestic product and the per-capita emergy ecological footprint. Therefore, adjusting the energy consumption structure, decreasing dependence on non-renewable energy, increasing the diversity of bioproductive land types and developing high-level tertiary industries are conducive to promoting Qingdao's sustainability. Additionally, the results provide a scientific reference and decision-making basis for regional sustainable development.